New Discovery of a Rare Robertsonian Translocation (15;22) - A Case report from India - Dutta, Atreyee; Banerjee, Byapti; Roy, Sanchita; Halder, Ajanta (Archives of Case Reports, 2024)
The rob(15;22) is one of the rarest translocations which accounts for only 0.6% of the entire Robertsonian translocations reported in humans. A case of rob(15;22) in association with trisomy 21 still has not been reported. In the present study, a case of a 3-year 6-month-old male child with rob(15;22) with trisomy 21 is focused. The phenotype comprises generalized hypotonia, delayed developmental milestones, simian crease, dysmorphic facies, etc. Chromosome analysis with peripheral blood was executed and the karyotype was interpreted as 46,XY,der(15;22)(q10;q10)+21. To analyse whether the chromosomal translocation was de-novo or inherited, the chromosome analysis with the peripheral blood of his parents was performed. The karyotype of the father was interpreted as 46,XY, and of the mother was 45,XX,der(15;22). It was concluded that the rob(15;22) was inherited from his mother, although trisomy 21 was a de novo incidence. Hence, this case study can be proven useful in the understanding of rob(15;22) in solo and rob(15;22) in association with trisomy 21.